Effects of chemically heterogeneous nanoparticles on polymer dynamics: insights from molecular dynamics simulations. Issue 7 (19th January 2018) - Zheng, Zijian; Li, Fanzhu; Liu, Jun; Pastore, Raffaele; Raos, Guido; Wu, Youping; Zhang, Liqun
Abstract : The dynamics of polymer melts embedding heterogeneous nanoparticles is investigated on varying the temperature and the nanoparticle composition. Abstract : The dispersion of solid nanoparticles within polymeric materials is widely used to enhance their performance. Many scientific and technological aspects of the resulting polymer nanocomposites have been studied, but the role of the structural and chemical heterogeneity of the nanoparticles has just started to be appreciated. For example, simulations of polymer films on planar heterogeneous surfaces revealed unexpected, non-monotonic activation energy to diffusion on varying the surface composition. Motivated by these intriguing results, here we simulate via molecular dynamics a different, fully three-dimensional system, in which the heterogeneous nanoparticles are incorporated in a polymer melt. The nanoparticles are roughly spherical assemblies of strongly and weakly attractive sites, in fractions of f and 1 − f, respectively. We show that the polymer diffusion is still characterized by a non-monotonic dependence of the activation energy on f . The comparison with the case of homogeneous nanoparticles clarifies that the effect of the heterogeneity increases on approaching the polymer glass transition.